Thermomechanical properties of polymers at high rates of strain - Trojanowski, A; Trojanowski, Albin S (1997)
The objective of this project was to develop a suitable testing technique which will allow the measurement of the bulk surface temperature of a specimen during high strain-rate compression testing. A fast response infra-red radiometer was developed which has the capability of measuring bulk surface temperature changes with an estimated accuracy of ±2°C and with a response time of 1.4μs. The radiometer is capable of measuring temperature changes above 20°C, when the signal-to-noise ratio becomes greater than 1. The properties of polymeric materials are extremely temperature sensitive, particularly when the glass transition temperature is approached. Models such as Eyring predict the yield of a polymer at constant temperature; the yield stress being unaffected by temperature rises. Temperature as well as mechanical data will allow models to be revised to include strain and dynamic temperature terms to predict the flow under adiabatic conditions. Strain-rates of ca. 2500s-1 were achieved when testing specimens and this rate was obtained using a split Hopkinson pressure bar. A substantial number of preliminary tests were conducted in order to obtain a suitable specimen size which was then used in the temperature measurement process. Quasistatic, intermediate and high strain-rate tests were performed; the last utilised the radiometer for temperature measurement. An Eyring plot was constructed from which fundamental values for activation volumes and enthalpies were obtained. Full descriptions of the testing techniques used have been included and a brief photoelastic analysis has been carried out on a partially deformed specimen which shows molecular alignment.